Wireless sensor networks: an overview from an optimization perspective - Shoukat Ali, Haroon; Mohamad Ali, Noor Azian (International Journal of Science and Research, 2014)
Wireless Sensor Networks (WSNs) have established themselves as the modern and future standard when it comes to networking applications. Wireless Sensor Networks (WSNs) are self-configured, infrastructure-less and consist of numerous nodes, which form the network structure. They have seen a variety of use in modern measurement and environmental analysis applications over the recent years and such applications of wireless sensor networks are being continuously studied and developed for even better overall performance. The nature and setup of wireless sensor networks allows for some important applications such as monitoring physical and environmental conditions like temperature, sound, vibrations, pressure and motion. As per the wireless sensor network structure, these measurements are then transferred to sinks and base stations from the nodes, for further study and analysis, basically the usage of data. This wireless sensor network standard does come with a few of its own problems, which range from coverage, topology, routing to energy efficiency. This paper discusses wireless sensor networks, and major problems related to the functioning of these networks and some related solutions. This paper also further proposes a theoretical solution to the energy efficiency problem of wireless sensor networks, and further studies how solving this problem can improve on some of the major existing applications of wireless sensor networks.